Studies on Characterization of Corn Cob for Application in a Gasification Process for Energy Production - Anthony I. Anukam; Boniswa P. Goso; Omobola O. Okoh; Sampson N. Mamphweli (Journal of Chemistry)
Quintessential characteristics of corn cob were investigated in this study in order to determine its gasification potential. Results were interpreted in relation to gasification with reference to existing data from the literature. The results showed that the gasification of corn cob may experience some challenges related to ash fouling, slagging, and sintering effects that may be orchestrated by high ash content recorded for corn cob, which may contribute to increasing concentration of inorganic elements under high temperature gasification conditions, even though EDX analysis showed reduced concentration of these elements. The study also found that the weight percentages of other properties such as moisture, volatile matter, and fixed carbon contents of corn cob as well as its three major elemental components (C, H, and O) including its clearly exhibited fiber cells make corn cob a suitable feedstock for gasification. FTIR analysis revealed the existence of –OH, C–O, C–H, and C=C as the major functional group of atoms in the structure of corn cob that may facilitate formation of condensable and noncondensable liquid and gaseous products during gasification. TGA results indicated that complete thermal decomposition of corn cob occurs at temperatures close to 1000°C at a heating rate of 20°C/min.